Alberta Infant Motor Scale (AIMS) Performance of Greek Preterm Infants: Comparisons With Full-Term Infants of the Same Nationality and Impact of Prematurity-Related Morbidity Factors. Issue 7 (1st July 2016) - Syrengelas, Dimitrios; Kalampoki, Vassiliki; Kleisiouni, Paraskevi; Manta, Vassiliki; Mellos, Stavros; Pons, Roser; Chrousos, George P.; Siahanidou, Tania
Abstract: Background: Only a few studies have been conducted with the objective of creating norms of the Alberta Infant Motor Scale (AIMS) for the assessment of gross motor development of preterm infants. The AIMS performance of preterm infants has been compared with that of the Canadian norms of full-term infants, but not with that of full-term infants of the same nationality. Moreover, the possible impact of prematurity-related morbidity factors on AIMS performance is unknown. Objectives: The aims of this study were: (1) to evaluate AIMS trajectory in a large population of Greek preterm infants and create norms, (2) to compare it with the AIMS trajectory of Greek full-term infants, and (3) to examine the possible influence of neonatal morbidity on AIMS scores in the preterm sample. Design: This was a cross-sectional study. Methods: Mean AIMS scores were compared, per month (1–19), between 403 preterm infants (≤32 weeks of age, corrected for prematurity) and 1, 038 full-term infants. In preterm infants, the association of AIMS scores with respiratory distress syndrome (RDS), intraventricular hemorrhage (IVH) of grade ≤III, bronchopulmonary dysplasia (BPD), retinopathy of prematurity (ROP), and sepsis was assessed by hierarchical regression analysis. Results: Alberta Infant Motor Scale scores were significantly lower in preterm infants than in full-term infants. Mean AIMS scores in preterm infants were significantly associated with RDS (b=−1.93; 95% CI=−2.70, −1.16), IVH (b=−0.97; 95% CI=−1.69, −0.25), and ROP (b=−1.12; 95% CI=−1.99, −0.24) but not with BPD or sepsis in hierarchical regression analysis. Conclusions: Alberta Infant Motor Scale norms were created for Greek preterm infants. This study confirms that AIMS trajectories of preterm infants are below those of full-term infants of the same nationality. The influence of morbidity factors, including RDS, IVH, and ROP, should be taken into account when administering the AIMS in preterm infants.